Addiction workforce development in Aotearoa New Zealand. (2nd November 2017) - Nelson, Anna
Abstract: This article provides an overview of addiction workforce development in Aotearoa New Zealand. Workforce development and workforce planning in the Aotearoa New Zealand context are briefly defined and followed by what the author believes are four noteworthy components of the New Zealand situation. The article addresses how Dapaanz (the addiction practitioners association and registering body); Matua Rak i (the addiction workforce development programme); the role of lived experience and recovery, and the Māori addiction workforce have been instrumental in the development of New Zealand's unique addiction sector.